Milady's skin care and cosmetic ingredients dictionary - Michalun, Michalun (Milady Thomson Learning, 2001)
An expanded section on skin physiology and chemical concepts enables the reader to better understand product performance through a thorough explanation of how chemicals and ingredients interact. The various skin types, conditions, and appropriate ingredients for treatments provide a quick reference to address clients' needs. This enlarged second edition contains over 2,000 ingredients including 200 new and updated entries. Expanded information on antioxidants and their stability, new discussion on aging and sensitive skin, and function of SPF and new sunblock ingredients offering full spectrum sunscreen and sunblock for both UVA and UVB rays has been added. A complete glossary of terms found in the skin physiology section familiarizes readers with the terminology used by chemists, and an appendix cross-referencing Latin botanical names with commonly used names complete this reference